2019
DOI: 10.3389/fnins.2019.01095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-invasive Brain Stimulation on Stimulant Craving in Users of Cocaine, Amphetamine, or Methamphetamine: A Systematic Review and Meta-Analysis

Abstract: Dopamine system plays a pivotal role in specific kinds of substance use disorders (SUD, i. e., cocaine and methamphetamine use disorders). Many studies addressed whether dopamine-involved craving could be alleviated by non-invasive brain stimulation (NIBS) techniques. Nevertheless, the outcomes were highly inconsistent and the stimulating parameters were highly variable. In the current study, we ran a meta-analysis to identify an overall effect size of NIBS and try to find stimulating parameters of special not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 77 publications
(91 reference statements)
3
42
0
Order By: Relevance
“…even when faced with consequences, subjects continue to pursue the drug) (Hu et al, 2019), the possibility of using rTMS to stimulate hypoactive prefrontal cortical neurons, which can then modulate interconnected networks, is appealing (Diana et al, 2017;Madeo and Bonci, 2019;Song et al, 2019). An increasing number of studies have shown anticraving effects following rTMS treatment targeting the PFC (see Ma et al, 2019;Madeo and Bonci, 2019;Zhang et al, 2019), presumably through modulation of the efferent glutamatergic and afferent dopaminergic connections (Diana, 2011;Diana et al, 2017; Figure 1). Therefore, rTMS modulation of mesocorticolimbic pathways in people with substance use disorders may provide therapeutic effects.…”
Section: Rtms In Cocaine and Methamphetamine Abuse -Clinical Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…even when faced with consequences, subjects continue to pursue the drug) (Hu et al, 2019), the possibility of using rTMS to stimulate hypoactive prefrontal cortical neurons, which can then modulate interconnected networks, is appealing (Diana et al, 2017;Madeo and Bonci, 2019;Song et al, 2019). An increasing number of studies have shown anticraving effects following rTMS treatment targeting the PFC (see Ma et al, 2019;Madeo and Bonci, 2019;Zhang et al, 2019), presumably through modulation of the efferent glutamatergic and afferent dopaminergic connections (Diana, 2011;Diana et al, 2017; Figure 1). Therefore, rTMS modulation of mesocorticolimbic pathways in people with substance use disorders may provide therapeutic effects.…”
Section: Rtms In Cocaine and Methamphetamine Abuse -Clinical Researchmentioning
confidence: 99%
“…In clinical studies, HF-rTMS over the DLPFC has been shown to have anticraving effects (for an overview, see Ma et al, 2019). Most studies apply chronic stimulation (i.e.…”
Section: Hz or Greatermentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling disorder has similar behavioral and pathophysiological manifestations as SUDs, suggesting potential overlap in dysregulation and interventional tools for treatment. In treating SUDs with rTMS, these reviews highlight the importance of considering both dopamine and glutamate (Moretti et al, 2020) as well as assessing individual differences in patients (Ma et al, 2019) to better uncover the known unknown of the underlying mechanisms of rTMS interventions. Also, applying high frequency stimulation (∼5-20 Hz) is more effective than low frequency (∼1 Hz) at reducing craving post-rTMS (Ma et al, 2019).…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…In treating SUDs with rTMS, these reviews highlight the importance of considering both dopamine and glutamate (Moretti et al, 2020) as well as assessing individual differences in patients (Ma et al, 2019) to better uncover the known unknown of the underlying mechanisms of rTMS interventions. Also, applying high frequency stimulation (∼5-20 Hz) is more effective than low frequency (∼1 Hz) at reducing craving post-rTMS (Ma et al, 2019). This reflects the shift toward implementing the high frequency, and shorter to implement, continuous and intermittent theta-burst stimulation (c/iTBS) protocols (Huang et al, 2005) than other rTMS protocols.…”
Section: Overview Of the Special Issuementioning
confidence: 99%